Desenvolvimento conceitual de um equipamento para separação de cinzas de caldeira - Bertochi, Renan Gasperin (2025)
Agro-industries are important contributors to employment and regional development in the areas where they are established. However, it is essential that they not only care for the environment but also ensure proper separation of materials to reduce productivity costs. The project presented in this work aims at the correct disposal of ash, addressing the issue that it contains a large amount of impurities that increase its final price, costs that are borne by the industries, especially materials such as stones and charcoal. Furthermore, the ash processed in the final stage of the boiler exits at high temperatures, making product collection difficult and posing risks to workers. The project development was carried out based on the methodology proposed by Pahl et al. (2005), structured in the stages of task definition, concept, preliminary design, and detailing. The study results in the presentation of a functional equipment concept, with evaluation of its technical and economic feasibility, promoting operational improvements, process safety, and sustainability in the reuse of generated waste.